Why Rhetoric and Ethics? Revisiting History/Revising Pedagogy - Lois Agnew (Journal of the Assembly for Expanded Perspectives on Learning, 2016)
Coupling rhetoric and ethics has helped create a coherent undergraduate writing major in one of the nation’s first free-standing composition programs.